A crevice corrosion assessment method for joints of mechanical components sealed with composite structure gaskets – The case of the engine cylinder head/mono-block joint. (January 2021) - Farfan-Cabrera, Leonardo Israel; Rodríguez-Bravo, Gerardo Alejandro; Godínez-Salcedo, Jesús Gilberto; Resendiz-Calderon, Cesar David; Salgado-Sviercovich, Juan Sebastian; Moreno-Ríos, Marisa
Highlights: An accelerated test to evaluate crevice corrosion in joints is presented. The joint study case (cylinder head, gasket and mono-block) was studied. Three aluminum alloys from different cylinder heads were evaluated. Corrosion rates, crevices volume and potentiodynamic behavior were obtained. Abstract: A test to evaluate crevice corrosion in joints of mechanical components sealed with composite structure gaskets in corrosive environments is presented. The crevice corrosion produced in joints comprising the cylinder head, gasket and mono-block was aimed as a study case to illustrate the test. It is based on polarization resistance and potentiodynamic polarization measurements obtaining localized and measurable crevice corrosion on small specimens in a short time. Corrosion rates, crevices volumes and potentiodynamic behavior of assembly specimens made of three different aluminum alloys extracted from actual cylinder heads and mono-blocks, and sections of cylinder head gasket were obtained and reported.